THE EFFECT OF TAX PLANNING, COMPANY VALUE, AND LEVERAGE ON INCOME SMOOTHING PRACTICES IN COMPANIES LISTED ON JAKARTA ISLAMIC INDEX - Megarani, Novia; Warno, Warno; Fauzi, Muchammad (Journal of Islamic Accounting and Finance Research, 2019)
Purpose - The purpose of this paper is to identify the effect of tax planning, company value, and leverage on income smoothing practice in companies listed on the Jakarta Islamic Index for the period 2010-2017.Method - The data in this study consisted of 12 companies listed on the Jakarta Islamic Index for the period 2010-2017. Samples are selected using the purposive sampling method. Eckel Index classification uses two types of earning as the target of incomee smoothing, namely operating income and income before tax. Hypothesis testing uses a logistic regression analysis model.Result - Result of simultaneously logistic regression tests tax planning, company value, and leverage affect income smoothing. And results of the partial logistic regression test of company value variable have a significant effect on income smoothing practices, while the tax planning and leverage variables have no significant effect on income smoothing practices.Implication - This study proves that tax planning, corporate value, and leverage simultaneously have a significant effect on income smoothing practices but partially not so that there are many variables that play a role.Originality - The research is the first study that describe use sharia relate income smoothing.